Prenatal and Postnatal Exposure to Ambient Air Pollution and Preschool Asthma in Neonatal Jaundice Infants - Chung HW; Hsieh HM; Lee CH; Lin YC; Tsao YH; Wu HW; Kuo FC; Hung CH (Dove Medical Press, 2022)
Hao-Wei Chung,1- 3 Hui-Min Hsieh,4- 7 Chung-Hsiang Lee,1 Yi-Ching Lin,5,8- 10 Yu-Hsiang Tsao,5 Huang-Wei Wu,3 Fu-Chen Kuo,11,12 Chih-Hsing Hung1,3,13- 15 1Department of Pediatrics, Kaohsiung Medical University Hospital, Kaohsiung, Taiwan; 2Department of Biological Science and Technology, National Yang Ming Chiao Tung University, Hsinchu, Taiwan; 3Department of Pediatrics, Kaohsiung Municipal Siaogang Hospital, Kaohsiung, Taiwan; 4Department of Public Health, Kaohsiung Medical University, Kaohsiung, Taiwan; 5Department of Medical Research, Kaohsiung Medical University Hospital, Kaohsiung, Taiwan; 6Department of Community Medicine, Kaohsiung Medical University Hospital, Kaohsiung, Taiwan; 7Center for Big Data Research, Kaohsiung Medical University, Kaohsiung, Taiwan; 8Division of Pharmacology and Toxicology, Department of Medical Research, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung, Taiwan; 9Department of Laboratory Medicine, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung, Taiwan; 10Doctoral Degree Program of Toxicology, College of Pharmacy, Kaohsiung Medical University, Kaohsiung, Taiwan; 11Department of Obstetrics & Gynecology, E-Da Hospital, Kaohsiung, Taiwan; 12School of Medicine, College of Medicine, I-Shou University, Kaohsiung, Taiwan; 13Research Center for Environmental Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 14Department of Pediatrics, Faculty of Pediatrics, College of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 15Graduate Institute of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, TaiwanCorrespondence: Fu-Chen Kuo, School of Medicine, College of Medicine E-Da Hospital, I-Shou University, No. 1, Yida Road, Yanchao Shiang, Kaohsiung, 824, Taiwan, Tel/Fax +886-7-6150940, Email ed100418@edah.org.tw Chih-Hsing Hung, Department of Pediatrics, Kaohsiung Municipal Hsiao-Kang Hospital, No. 482, Shanming Road, Siaogang District, Kaohsiung City, 812, Taiwan, Tel +886-7-3121101-6506, Fax +886-7-3213931, Email pedhung@gmail.comPurpose: Both air pollutant exposure and neonatal jaundice (NJ) have known effects on childhood asthma, but a higher total serum bilirubin (TSB) level has been associated with lung protection. This study aimed to assess whether prenatal/postnatal exposure to ambient air pollutants is related to the development of asthma in infants with NJ.Patients and Methods: A nested case-control retrospective study was performed using the data of infants with NJ in the Kaohsiung Medical University Hospital Research Database. Data on average ambient air pollution concentrations within six months, the first year and second year after birth, and in the first, second and third prenatal trimesters were collected. NJ was defined as TSB levels ≥ 2 mg/dl with the diagnosis less than one-month-old. Asthma was defined as a diagnosis with medication use. We constructed conditional logistic regression models to estimate adjusted odds ratios (aORs) and 95% confidence intervals (CIs).Results: Exposure to NO and SO2 at all six time points in the study was significantly associated with an increased risk of preschool asthma in infants with NJ. The overall peak OR (95% CI) of SO2, PM2.5, PM10, NO, NO2, and NOX were 1.277 (1.129- 1.444), 1.057 (1.023- 1.092), 1.035 (1.011- 1.059), 1.272 (1.111- 1.455), 1.168 (1.083- 1.259) and 1.104 (1.051- 1.161), respectively. Fetuses in the first and second trimester were most vulnerable to ambient air pollutant exposure such as SO2 PM2.5, NO, NO2 and NOX during the prenatal period. Exposure to all six ambient air pollutants during the first and second years after birth significantly affected preschool asthma in NJ infants.Conclusion: In different time windows, prenatal and postnatal exposure to SO2, PM2.5, PM10, NO, NO2, and NOX were associated with preschool asthma in NJ infants. The relatively high impact of NO and SO2 exposure in infants with NJ requires further studies and prevention measures.Keywords: 1000 days, air pollution, SO2, neonatal hyperbilirubinemia, asthma